Stacky Hamiltonian Actions and Symplectic Reduction. (11th March 2020) - Hoffman, Benjamin; Sjamaar, Reyer
Abstract: We introduce the notion of a Hamiltonian action of an étale Lie group stack on an étale symplectic stack and establish versions of the Kirwan convexity theorem, the Meyer–Marsden–Weinstein symplectic reduction theorem, and the Duistermaat–Heckman theorem in this context.